The first complete mitochondrial genome sequence of the korean endemic catfish Silurus microdorsalis (Actinopteri, Siluriformes, Siluridae). Issue 1 (2nd January 2020) - Park, Chang Eon; Park, Yeong-Jun; Kim, Min-Chul; Park, Min-Kyu; Jung, YeonGyun; Choi, Seung-Dae; Jo, YoungJae; Kang, Gi-Ung; Kim, Min-Ji; Li, Qing X.; Yoza, Brandon A.; Kim, Kgu-Hwan; et al.
Abstract: The Silurus microdorsalis is known as Korean endemic slender catfish. Despite its value as a biological resource, there is no complete mitochondrial genome sequence. The complete mitochondrial genome consisted of 16, 524 bp including 22 transfer RNA (tRNAs), 2 ribosomal RNA (rRNAs), 13 protein-coding genes (PCGs), and A + T rich region. The overall base composition of S. microdorsalis was A + T: 56.1%, C + G: 43.9%, apparently with slight AT bias. Phylogenetic relationship showed that S. microdorsalis was closely related to Silurus glanis.